Solvability and Stability for Singular Fractional $(p, q)$-Difference Equation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we initiate the solvability and stability for a classof singular fractional $(p, q)$-difference equations. First, we obtain an existencetheorem of solution for the fractional $(p, q)$-difference equation. Then, by usinga fractional $(p, q)$-Gronwall inequality, some stability criteria of solution areestablished, which also implies the uniqueness of solution.
Keywords: Fractional $(p; q)$-difference equation; Existence of solution; Stability; $(p; q)$-Gronwall inequality; Uniqueness.